The Impact Of Population Growth Index Over GDP Per Capita Index At The Republic Of Korea - الغرير موسى; السعدي هبة (Latakia University Journal - Economic and Legal Sciences Series, 2021)
This research highlights the importance of human capital as a vital productive element, in terms of the dialectic between those who advocate curbing population growth and those who advocate the importance of investing efficiently and effectively, and based on the GDP per capita index as one of the vehicles of the Economic Welfare Appreciation Index, which is the first step to rise into sustainable development, away from the scourge of poverty. This research presented the Republic of Korea, which chose the path of investing in the human element and raised its industry from the bottom of the value-added ladder to the top of the ladder, achieving escalatory rates of population growth, per capita GDP and growing rates of economic growth. The Republic of Korea was able to activate the role of the human capital component in the production process with the possibility of increasing its share of GDP. As an example to the Syrian Arab Country, which is rich in this element and for other developing countries. The research concluded that the impact of increased population growth on GDP Per Capita depends on the role played by the earlier in the development process, as determined by the economic and political decision-maker. Investment in human capital is also the hallmark of growth, progress and economic well-being that elevates the economy to sustainable economic development and is the main driver of industrial revolutions and technological prosperity.